THE MAIN CHARACTER'S INNER CONFLICT IN THE NOVEL “ILAIKA HARUUFI” (ABRAHAM MASLOW'S HIERARCHY OF NEEDS) - Najwa Khairia; Moh Zawawi (LLDIKTI Wilayah X, 2024)
Inner conflict plays a crucial role in character and story development in literature, particularly in novels. This research highlights how inner conflict arises when fundamental human needs such as physiological, safety, belonging, self-esteem, and self-actualization are unmet or in conflict. Using a descriptive qualitative method, the study analyzes Aya Mohrat’s novel Ilaika Haruufi and draws on related secondary articles. Data are analyzed through triangulation techniques, involving data reduction, presentation, and conclusion. Findings reveal that inner conflicts in Ilaika Haruufi, including sadness, disappointment, stress, frustration, trauma, and confusion, stem from unmet basic needs. These conflicts deepen the psychological complexity of the main character and shape the narrative and themes expressed by the author.